Gout of the iliopsoas muscle combined with tuberculosis infection causing persistent fever: a case report and literature review - Zhang, Mei-Ren; Hu, Jian-Hui; Guan, Jian-hao; Zeng, Xiao; Chen, Hai-Yun (Frontiers in Medicine, 2026)
BackgroundGout involves the deposition of monosodium urate (MSU) crystals in the body, which can have varied presentations but commonly presents in the peripheral joints. However, gout of the iliopsoas muscle is extremely rare. Moreover, the literature on gout of the iliopsoas muscle combined with tuberculosis (TB) infection—which can mimic common pelvic abscesses—is more limited.Case presentationA case of a psoas muscle abscess with a persistently high fever following gout of the iliopsoas muscle, combined with tuberculosis infection, is reported in this study. We present the case of a 71-year-old woman who presented with deep, diffuse pain in the lower back and left hip and a persistently high fever for 1 week. She showed no response to systemic anti-infective treatment. A dual-energy computed tomography (CT) scan showed multiple bilateral gout nodules around the iliac bone, sacrum, and proximal femur. A contrast-enhanced magnetic resonance imaging (MRI) scan revealed a large hyperdense cystic lesion extending along the iliopsoas muscle and erosion and widening of the left sacroiliac joint. The patient received open surgical intervention to achieve effective drainage via a para-rectus approach. Some milky tophi were scraped from the cystic lesion in the iliopsoas muscle. Intraoperative pathology of these tissues confirmed gout formation. High-throughput gene sequencing of these tissues detected various divergent mycobacterium tuberculosis, without evidence of other bacteria, fungi, or anaerobic bacteria. A diagnosis of a pyogenic psoas abscess due to gout of the iliopsoas muscle, combined with tuberculosis infection, was made. The patient responded well to the therapy and had an uncomplicated recovery after anti-gout and anti-tuberculosis treatment.ConclusionThe development of an iliopsoas abscess as a consequence of gout in the iliopsoas muscle combined with tuberculosis infection is rare. Making a diagnosis in such an unusual case can be challenging. For patients with unexplained high fever as the main clinical symptom, systemic anti-infective treatment alone may not be effective. High-throughput gene sequencing for various pathogens is very helpful in identifying the cause of the pathogen. Open surgical intervention using a para-rectus approach for effective drainage is highly effective and a routine procedure.